Pendukung Keputusan Menentukan Tingkatan Kualitas Teh Kayu Aro Dengan Cara Penerapan Metode Analytical Hierarchy Process (AHP) (Studi Kasus Di PTPN IV Kayu Aro) - ADEK CHANDRA; HAIRUL CANDRA (JURNAL ILMU PENGETAHUAN & SISTEM INFORMASI (JIPSI), 2018)
ABSTRACT In the process of quality assessment Kayu Aro tea using tea organoleptic experts often encountered obstacles sensory limitations of the people judge. Based on these constraints we conducted a study using Analytical Hierarchy Process (AHP). This method aims to see the extent to which the quality assessment Kayu Aro so as to document the experiences of the tester Kayu Aro tea, but it can also correct the results of quality assessment conducted Kayu Aro by the tester. Based on the test manual processes and applications Exsper Choice, the results of the assessment testerdan assessment results by using AHP not significantly different. AHP method can be used as a method of quality assessment quality assessment results Kayu Aro. AHP method can not be used if the difference between the assessment done by the tea tester tester and others are too far. Keywords : Decision Support Systems, Analytical Hierarcy Process (AHP), Software Expert Choice, Tea Kayu Aro.